Anthrax revisited: how assessing the unpredictable can improve biosecurity - Sabra, Dunja Manal; Krin, Anna; Romeral, Ana Belén; Frieß, Johannes Ludwig; Jeremias, Gunnar (Frontiers in Bioengineering and Biotechnology, 2023)
The zoonotic bacterial pathogen B. anthracis is the etiological agent of peracute, acute, subacute, and chronic anthrax, an often fatal toxin-mediated disease primarily affecting herbivores, but also encountered in other mammals, including humans, and occasionally birds. B. anthracis is one of the high-priority and most dangerous biological weapon agents of statesponsored bioweapon programs since World War I. Anthrax was also employed in terrorist and bio-crime attacks causing enormous economic damage and societal disruption. This study transdisciplinarily explores many intertwined fields within public health, natural science and security studies to question the widespread narrative, that significant advances in science and technology could increase the anthrax biothreat and its accessibility to a broader realm of actors. It evaluates if and how synthetic biology, genome editing, information availability, and other emerging and converging sciences and technologies would impact a contemporary attempt to use B. anthracis as a weapon of bioterror. Drawing on novel countermeasure capabilities including diagnostics, treatment, decontamination and prevention, this study suggests necessary biosecurity architecture adaptation to prevent a bioterrorist anthrax attack from occurring and/or protect against it, to increase the ability to react during such an event, and to mitigate its subsequent impact. Being the first of its kind, it will be of value for all involved stakeholders and hopefully raise awareness in the broader scientific community.